Optimization of the Angso Duo Tourism Market Area Based on the Historic Riverfront of the Batanghari River, Jambi City - Yulistian Saldi (Sustainability (STPP) Theory, Practice and Policy, 2023)
Angso Duo Market or also known as the Tanah Select Pesako Betuah location is an area that has a long history in the development of the city of Jambi. Angso Duo Market, which is located on the Batanghari River, is one of the development locations for riverside tourist areas which has great potential for development. Many historical events occurred at this location which brought many memories to the people of Jambi. This area has significant historical value as the historic Riverfront Batanghari river site, which has witnessed the cultural and social development of the surrounding community. The aim of this research is to identify and design an optimization strategy for the Angso Duo Tourism Market Area based on the historical heritage of the Batanghari River Riverfront which produces design aspects of the waterfront tourist area which are the basis for determining the design approach, namely the Collective Memory and Sense approaches. of Place (Meaning of Place). The research methods used in this research are literature study, field survey, interviews with related parties, and data analysis. The research results show that the Angso Duo Tourism Market Area has the potential to become an attractive tourist destination. The history of the Batanghari Riverfront, which has existed for many years, is the main attraction. However, efforts are still needed to optimize the use of this area. Based on the research results, several optimization strategies are recommended, including: Historical Heritage Conservation, Preserving and maintaining historical sites around the Batanghari River Riverfront to maintain the authenticity and historical value of the area. Infrastructure Development, Improving regional infrastructure, including road access, parking areas and other public facilities, to increase visitor comfort. Development of tourist facilities, building tourist facilities and facilities that support visitor activities, such as children's play areas, places to eat and places to rest. Environmental Management, Developing a sustainable environmental management plan to preserve the Batanghari River and its surroundings. By implementing this strategy, it is hoped that the Angso Duo Tourism Market Area can become an attractive and sustainable tourist destination, providing economic and social benefits for the local community, as well as preserving the history and environment of the Batanghari River.